The impact of development funding on community development : a case study of the National Development Agency in Makhuduthamaga Municipality in the Limpopo Province - Lentswane, Moloke Peter (University of Limpopo (Turfloop Campus), 2013)
The study aims to provide insights into the nature and extent of development funding provided to various poverty eradication projects by the National Development Agency (NDA) and its subsequent impact on reducing poverty in the predominantly rural communities of the Makhuduthamaga Municipality in the Limpopo Province. It examines in detail the impact made by the NDA on community development through the disbursement of funds to poverty eradication projects. It also provides insights into the total number of the NDA-funded projects and the total proportion of the NDA-funds allocated to them in the Makhuduthamaga Municipality. The study further examines the nature of the NDA support regarding the design of the interventions, relevance, participation of communities, delivery modalities and sustainability. The effectiveness of the NDA-funded projects in community development is determined using employment opportunities created, income generated, skills transferred, assets accumulated, sustainability mechanisms and community empowerment indicators. Although all of these indicators are found to be tightly linked to the NDA’s mandate of poverty eradication, the extent to which the NDA has achieved its objectives in disbursing development funding earmarked for poverty eradication and strengthening of CSOs was yet to be determined, hence the relevance of this study. The study, therefore, highlights key issues regarding the types of employment opportunities created and levels of income emanating from the NDA-funded projects. The study further highlights various areas of community empowerment, financial and sustainability measures put in place for the sustainability of the NDA-funded projects. Using a combined method of research, that is the qualitative and quantitative case study approach, the study highlights in detail insights into the impact made by the NDA on community development, particularly on Makhuduthamaga Municipality. The study highlights that while the NDA made some strides in the creation of employment opportunities, income generation, food security and community empowerment, both financial and institutional sustainability proved to be a daunting challenge for the NDA-funded projects Tailor-made and accredited training interventions coupled with the introduction of market-driven products to the NDA-funded projects as opposed to heavy reliance on donor funding will go a long way in bringing about productivity and, most probably, positive balance sheets and the maximum impact on the NDA funded projects.
Thesis (M.Dev.) -- University of Limpopo, 2013
Keywords: Develompent funding; Poverty eradication; Community development; 307.14; Community development; Rural development